Pembuatan Sampul Buku Novel Berjudul “Algoritma Konstanta Orion Dan Tursina” Karya Titin Pardesi - Kunto Adi Rumekso (Pusat Riset dan Inovasi Nasional, 2025)
The passage of time has brought about numerous changes in every field, including the creative industry, which has also been impacted by technological advancements. Written works considered high-quality are no longer judged solely on the basis of writing style or the substance of the text, but also on their visual presentation, with the aim of capturing consumers’ attention. Competition has become commonplace in the world of marketing, and various methods are employed to enhance market value; and this is also to be used in a creative writing. Authors of novels, poetry books, etc often collaborate with graphic designers or illustrators to enhance the appearance of their books through visual designs on the cover or the illustrations within the text—a practice that is widely adopted as a means to support promotion and boost sales appeal.